DESAIN PEMBELAJARAN KIMIA BERMUATAN NILAI PADA SUBTOPIK PERKEMBANGAN MODEL ATOM - Wulandari, Rina (2014)
Penelitian yang berjuduldesainpembelajarankimiabermuatannilaipadasubtopikperkembangan model atomdilakukanuntukmembuatdesainpembelajarankimiabermuatannilaipadasubtopikperkembangan model atom yang dituangkandalambentukRPPdanperangkatnya (LKS).Metodepenelitian yang digunakanadalahdeskriptif.Instrumen yang digunakanadalahformatkesesuaiandesainpembelajarandenganacuandanlembarvalidasi.Hasilpenelitianmenunjukkanbahwadesainpembelajaranbermuatannilaipadasubtopikperkembangan model atom yang telahdibuatsudahsesuaidenganacuandandinyatakan valid dengannilai CVR darisetiap item yang melebihinilai CVR minimum (0,622).Karakteristikdesainpembelajaranbermuatannilaipadasubtopikperkembangan model atomterdiriatasdirumuskannya 16tujuanpembelajaranaspekafektif; adanyamateripembelajaranbermuatannilai; dipilihnya modelpembelajarankooperatif-inkuiri, metodediskusi, pendekatanscientific,dan media pembelajaran (LKS)sebagaistrategipembelajaran yang dapatmenanamkannilaikepadasiswa; sertaadanyalembarpenilaianyang dapatmengevaluasinilai (lembarobservasi, lembarpenilaiandiri, danlembarpenilaiantemansejawat).Nilai-nilai yang dapatditanamkandarisubtopikperkembangan model atomadalahreligius, disiplin, kerjakeras, pedulisosial, dantanggungjawab.Rekomendasidaripenelitianinidiharapkanagar desainpembelajaranbermuatannilaiperludikembangkanuntukberbagaitopikmengingatpentingnyapenanamannilai-nilaikepadasiswa. The research about value contained instructional design of chemistry on subtopic the development of the Atomic model was conducted to make value contained instructional design of chemistry on subtopic the development of the Atomic model that set forth in the form in RPP format and it's devices (LKS). The research method that used is descriptive. The instrument that used is compatibility format instructional design with reference and validation sheet. Result of the research shows that value contained instructional design of chemistry on subtopic the development of the Atomic model that has been made is appropriate with reference and has valid with CVR score from each item that exceed CVR score minimum (0.622). The characteristic of the value contained instructional design of chemistry on subtopic the development of the Atomic model consist of the formulation 16 purpose of instructional affective aspect; the availability of the instructional materials that contain of value; to choose cooperative-inquiry instructional model, discussion method, scientific approach, and instructional media (LKS) as the instructional strategy that can be implanted value to students; and the existence of assessment sheet that can be evaluated value (observation, self assessment, and peer assessment). The values than can be implanted from subtopic the development of the Atomic model is religious, social care, cooperaion, tolerance, responsibilities, fair, discipline, the existence of the self, self-actualization, and responsive. The recommendation from this research is expected the value of instructional design can be developing for various topic considering how important the implantation of values to students.